El empleo subvencionado: entre las políticas activas de empleo y la mutación del salario - López Andreu, Martí; Verd Pericàs, Joan Miquel; Lope Peña, Andreu (Cuadernos de Relaciones Laborales, 2008)
In recent years national state policies in Europe have developed some mechanisms of subvention to employment with the objective of creating employment. This kind of subsidies, with different types of intervention, are often situated in the side of active policies, linked frequently with European employment strategy. The article derives from a comparative European research project that tries to establish differences and common tendencies in this question. In this sense, the article offers a conceptualisation of subsidised employment and its different types, especially on the Spanish case and compares it with other European countries. Finally, it shows some tendencies that announce that these interventions hint towards a wage relation mutation.